THE SOLUBILITY AND SPECIATION OF MOLYBDENUM IN WATER VAPOUR AT ELEVATED TEMPERATURES AND PRESSURES: IMPLICATIONS FOR ORE GENESIS - Rempel K.U.; Migdisov A.A.; Williams-Jones A.E. (My University, 2006)
The solubility of molybdenum trioxide in liquid-undersaturated water vapour has been investigated experimentally at 300, 320, and 360 °C and 39-154 bars. Results of these experiments show that the solubility of MoO3 in water vapour is between 1 and 29 ppm, which is 19-20 orders of magnitude higher than the vapour pressure of MoO3(g). Molybdenum solubility increases exponentially with fH2O, suggesting the formation of a gaseous hydrated complex of the type MoO3?nH2O by the reaction: (A. 1) MoO3(g) + nH2 O ? MoO3 ? nH2O(g) The hydration number, n, is interpreted to have a value of 2.0 ? 1.0 at 300 °C, 2.4 ? 0.6 at 320 °C, and 3.1 ? 0.3 at 360 °C. Values of log K for this reaction are 18 ? 5 at 300 °C, 16 ? 3 at 320 °C, and 12 ? 1 at 360 °C. Comparison with data from the literature shows that the solubility of MoO3?nH2O increases non-linearly with increasing fH2O, and that the hydration number is equal to the slope of the tangent to a function inferred from a plot of log fMoO3?nH2O versus log fH2O. The predominant species in water vapour at fH2O ? 1 bar is MoO3?H2O, whereas at the conditions of the present experiments it is MoO3 ?2-3H2O. Calculations based on the solubility of MoO3 in equilibrium with molybdenite at 600 °C and 500 bars, using average H2O and total S fluxes of actively degassing volcanoes, with fO2 and fS2 controlled by the assemblage hematite-magnetite-pyrite, indicate that the vapour phase can transport sufficient Mo in about 115,000 years (within the life of geothermal systems) to form a deposit of 336 Mt, with an average grade of 0.087% Mo (e.g., the Endako Mo-porphyry deposit, Canada). This suggests that vapour-phase transport of Mo is far more important than previously thought and should be given further consideration in modelling the formation of porphyry molybdenum deposits. ? 2005 Elsevier Inc. All rights reserved.
Keywords: METALLOGENESIS; MOLYBDENUM; ORE DEPOSIT; SOLUBILITY